Dampak Citra dan Karakteristik Produk terhadap Kepuasan Pelanggan serta Konsekuensinya terhadap Loyalitas Pelanggan UMKM Kuliner Sambal Bakar Lengkong di Kota Bandung - dadahmuliansyah (JURNAL EKONOMI, BISNIS DAN HUMANIORA, 2024)
The main challenges faced by MSMEs in the city of Bandung include low people's purchasing power, increasingly fierce competition, and risks related to customer loyalty. Based on this, this research aims to analyze the influence of product image and attributes on customer loyalty, both directly and indirectly through customer satisfaction. This research uses a quantitative approach in Bandung City, with the unit of observation being Sambar Bakar Lengkong customers. The sample used consisted of 235 respondents taken using the Multistage Random Sampling technique. Causality analysis was carried out using Structural Equation Modeling. The research results show that: The image and product attributes of Culinary MSMEs in the city of Bandung contribute to customer satisfaction, but do not have a direct effect on customer loyalty; Customer satisfaction has an important role in creating customer loyalty; Customer satisfaction functions as a mediator between the influence of product image and attributes on customer loyalty; Product attributes have a more significant influence than image in increasing customer satisfaction, which in turn will create customer loyalty. This research provides managerial insight to increase Sambar Bakar Lengkong customer loyalty, with a focus on increasing customer satisfaction supported by developing product attributes and image.